(untitled) (International Seven Journal of Multidisciplinary, 2025)
The pharmaceutical industry faces growing challenges in recruiting highly skilled professionals due to the high demand for specialists in areas such as research, development, and regulation. Hiring time, directly impacting productivity and project advancement, has become a strategic concern. The use of technologies such as artificial intelligence (AI) and digital recruitment platforms has accelerated this process by automating steps like resume screening, data analysis, and conducting initial interviews. Furthermore, collaboration with universities and research centers has contributed to the creation of pipelines for qualified candidates, optimizing hiring planning. To ensure an efficient recruitment process, pharmaceutical companies must adopt a well-defined structure and integrate HR efforts with marketing strategies. Transparency in recruitment and the use of talent attraction programs are key to reducing wait times and ensuring that positions are filled with highly skilled professionals. The adoption of ethical recruitment practices and collaboration with specialized headhunters are also essential to speeding up the process and ensuring the hiring of the best candidates. In the context of technological advancements, it is important for pharmaceutical organizations to implement solutions that promote fairness and objectivity, particularly in applying AI algorithms in the recruitment process. While technology helps eliminate biases, it is essential to ensure that hiring decisions are fair and transparent. Companies that adopt a strategic and ethical approach to recruitment will have better chances of attracting and retaining the best talent, driving their innovation and competitiveness in the global market.